Analisis Implementasi Aspek Keunikan Dalam Peradilan Agama Di Indonesia - Restu Teguh Imani; Moh. Imam Mahmudin; Yuli Agung Nugroho; Lintang Zufar Satyanagama; Nur Rofiq (International Forum of Researchers and Lecturers, 2024)
Religious Courts in Indonesia have unique, complex and interesting aspects, reflecting the diversity of religions and cultures in society. This uniqueness includes the legal basis, the role of religious courts in resolving religion-based conflicts, as well as the various challenges faced in ensuring justice. Religious Courts also present unique and interesting dynamics in the state justice system. The uniqueness of Religious Courts lies in the harmonization of religious law and national positive law, creating a unique and often complex legal framework. This article aims to describe and analyze the unique aspects of religious justice in Indonesia. With a deeper understanding of these challenges, efforts can be directed towards improving and developing the religious justice system so that it remains relevant and effective in handling legal conflicts related to religious aspects in Indonesian society. This research examines the implementation of unique aspects in the religious justice system in Indonesia. The religious justice system in Indonesia has unique characteristics that reflect various cultural, religious and social dimensions in a country with a diverse population. As a country with a majority Muslim population, religious courts play an important role in enforcing family and marriage laws based on Islamic law. This study underlines the importance of understanding the unique aspects of religious justice in Indonesia in the context of a legal state based on the supremacy of law. Ensuring a balance between local values, religion, and national positive law is a complex task, but essential to achieving justice in Indonesia’s rapidly evolving religious justice system.